Love as A Force for Women’s Liberation and Identity in Nadeem Aslam’s Maps for Lost Lovers: Love as A Force for Women’s Liberation and Identity - Aamer Shaheen; Sadia Qamar (The Journal of Humanities & Social Sciences, 2019)
The present study focusses on Nadeem Aslam’s use of love plot in his novel Maps for Lost Lovers (2004) as the means of showcasing resistance to a misogynist culture in a fictional multicultural town in England: Dasht-e-Tanhaii. The Chanda/Jugnu love plot, contextualizing the complicated dynamics of a multicultural society, serves the purpose of granting the female characters a peculiar sense of liberty and identity in the wake of an oppressive male dominant society and culture. The study reflects critically upon the Chanda/Jugnu love relationship by employing feminist thoughts of Gayatri Spivak supported with Erich Fromm’s ideas about love. Reading Aslam’s female characters, through Spivak’s (1988) perspective, as the speechless subalterns of the Third World, the paper endeavors to establish Aslam as a Third world, albeit male, intellectual who grants his female protagonist Chanda to pursue love as a speech action to defy her subalternity in a social milieu essentially designed by imperialist patriarchy. Fromm’s (1956) notion of learning and following the art of love, as a sole recourse to seek out solutions to the problems of human existence, remains a guiding principle to understand the Chanda/Jugnu love plot. The study, exploring Aslam’s use of women’s love as an emancipatory force helping them raise their voices to reclaim their freedoms and identities, is significant as amid other critically evaluated social issues presented in Maps for Lost Lovers, the issue of Love as an emancipatory force for women’s liberation and identity had remained neglected and in the background.